2014
DOI: 10.1093/neuonc/nou321
|View full text |Cite
|
Sign up to set email alerts
|

Late morbidity in long-term survivors of childhood brain tumors: a nationwide registry-based study in Finland

Abstract: Pediatric BT survivors had significant neurocognitive consequences. This, together with the considerable risk for endocrine morbidity, will motivate us to organize systematic follow-up procedures for pediatric BT survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 35 publications
1
26
2
Order By: Relevance
“…Radiation complications among 141 long-term survivors of retinoblastoma at the 5-year follow-up included non-proliferative maculopathy (25%), papillopathy (26%), cataract (31%), and glaucoma (11%) [ 198 ]. Ocular deficits are also common among survivors of CNS tumors [ 199 , 200 ]. Radiotherapy involving the eye is a risk factor for cataracts, legal blindness, dry eyes, and double vision [ 176 , 177 , 181 , 201 ].…”
Section: Neurosensory Deficitsmentioning
confidence: 99%
“…Radiation complications among 141 long-term survivors of retinoblastoma at the 5-year follow-up included non-proliferative maculopathy (25%), papillopathy (26%), cataract (31%), and glaucoma (11%) [ 198 ]. Ocular deficits are also common among survivors of CNS tumors [ 199 , 200 ]. Radiotherapy involving the eye is a risk factor for cataracts, legal blindness, dry eyes, and double vision [ 176 , 177 , 181 , 201 ].…”
Section: Neurosensory Deficitsmentioning
confidence: 99%
“…Central nervous system (CNS) cancers are the most frequently occurring solid tumors in children and most common cause of cancer deaths among children 0 to 14 years of age . Despite improvements in survival, morbidity remains high . Sleep disturbances are frequently reported during treatment and survivorship .…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal analysis of severe health problems such as those that require hospital admissions provides insight into the extent of chronic health conditions and healthcare consumption in CCS [7,8]. Previous research has shown that an increase in chronic health conditions among CCS translates into an increased risk of hospitalizations [9][10][11][12][13][14][15][16][17][18][19][20]. Several studies have thus provided important insight into the long-term morbidity in CCS using hospitalizations as a surrogate indicator [9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%